Pengaruh Motivasi Kerja dan Kompetensi terhadap Efektivitas Kerja Pegawai di Kantor Wilayah Pelayanan IV Perusahaan Umum Daerah Air Minum Kota Makassar - Gufrana Gufrana; Anwar Anwar; Burhanuddin Burhanuddin; Zainal Ruma; Tenri Sayu Puspitaningsih Dipoatmodjo (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze the influence of work motivation and competence on the work effectiveness of employees at the Regional Service Office IV of the Makassar City Regional Drinking Water Company. This study employed a quantitative research approach using a purposive sampling technique involving 100 employees responsible for customer service, administration, and daily operational activities. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression with SPSS version 26. Prior to hypothesis testing, the research instrument was tested for validity and reliability, while classical assumption tests were conducted to ensure the suitability of the regression model. The results indicate that work motivation and competence have a positive and significant effect on employee work effectiveness, both partially and simultaneously. Employees with higher motivation tend to demonstrate greater responsibility, productivity, and commitment, while higher competence enables employees to perform tasks more efficiently and accurately. These findings suggest that improving employee motivation through appropriate incentives and strengthening competencies through continuous training and development programs can significantly enhance organizational effectiveness and service quality. Therefore, management is encouraged to implement sustainable human resource development strategies to improve employee performance and achieve organizational objectives.